Estudos sobre a construção e uso de materiais manipuláveis no ensino de ciências naturais para estudantes com surdocegueira - Perassolo, Valquiria (Universidade Federal de São Carlos, 2023)
The school inclusion of people who are the target audience of Special Education is still one of the great challenges of Brazilian education. The large number of people excluded from the right of access to schooling is real and the issue is even more complex when it comes to people with disabilities, such as those with deafblindness. This research focuses on the education of children, adolescents and young people with deafblindness, who are socially invisible and who often have their right of access and permanence in education denied due to failures of the educational system to receive and include them. The main objective is to highlight and analyze the potentialities and challenges found on the use of manipulable materials in teaching of Natural Sciences for students with deafblindness. As methodology, the qualitative approach was the option of the kind of case research. Two deafblind students from the Center for Care and Support to the Deafblind (CEAADA) participated in the research, their guardians who participated in the interview to characterize them, two teachers who attended them in the year 2021, and two teachers who attended them in the year 2022. Propositions of manipulable materials used by teachers in teaching natural sciences to students with deafblindness were observed and materials were also made and supplied according to the students' needs. All these materials were handcrafted, that is, not industrialized. The analyzes were guided by the effort to understand the demands of schooling deafblind students and the potentialities and challenges as to the use of manipulable materials adopted for teaching such students. As a result, the data indicate that families consider the schooling process important, but show many difficulties in passing on the activities proposed by the teachers during remote teaching. The teachers participating in the research, although they have little experience in teaching students with deafblindness, they tried to research and adapted the activities that would be proposed. The participating teachers and the researcher established a partner relationship, in which they discussed and developed together the preparation of materials and activities proposed during the research period. The teachers proved that they have knowledge of what manipulable materials are and these materials show great potential in the teaching of these students, as they allow them to explore different textures, formats and sensations. It is also evident that the teachers notice the need for a differentiated pedagogy for teaching people with this disability.
Studies about the construction and use of manipulative materials in natural science teaching to students with deafblindness
Keywords: Educação especial; Educação em ciências naturais; Surdocegueira; Inclusão; Materiais manipuláveis; Special education; Education in natural sciences; Deafblindness; Inclusion; Manipulable materials; CIENCIAS HUMANAS::EDUCACAO